Progress in Studying Theoretical Models of NSSI Behavior in Adolescents - Long, LiuYan (Pacific International Journal, 2024)
Non-suicidal self-injury, NSSI refers to the individual in subjective without suicide intention, a series of not for the purpose of death, directly, intentionally, repeatedly hurt their organs and tissues, and objectively will not cause death, but cause mild or moderate damage, such as the skin cutting, friction, needles, scratch, this behavior can not be accepted by recognition or society. NSSI has become a serious impact on adolescent psychosomatic health worldwide public health problems, NSSI behavior is an important factor predicting suicide, the incidence of adolescent NSSI in China, the physical and mental health is closely related to its personal future development, about the family, social and national harmony and stability, should cause the attention of the whole society. NSSI may be related to many factors, such as psychological problems, family environment, campus atmosphere, and social relations. This paper summarizes the shortcomings of NSSI behavior theory model and analyzes the good understanding of the mechanism of adolescent NSSI behavior, provides the theoretical basis for adolescent NSSI research, provide the theoretical basis for NSSIR prevention, intervention program and policy formulation for health departments, education system and schools in China.